Konsep Khilafah dalam Surah Al Baqoroh ayat 30 (Studi komparasi Tafsir Fii Zhilalil Qur'an Karya Sayyid Qutb dan Tafsir Al-Azhar Karya Buya Hamka) - Fajriansyah, Bima; Rhain, Ainur; Dahliana, Yeti; Nurrohim, Ahmad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This study examines the concept of khilafah in Surah Al-Baqarah verse 30 through a comparative analysis of Tafsir Fii Zhilalil Qur’an by Sayyid Qutb and Tafsir Al-Azhar by Buya Hamka. Sayyid Qutb interprets khilafah as the implementation of Allah’s sovereignty on earth, emphasizing the application of Islamic law in all aspects of life, both individual and collective. His perspective is influenced by the socio-political conditions of 20th-century Egypt, marked by struggles for an Islamic governance system. In contrast, Buya Hamka views khilafah as a divine mandate that is not limited to political leadership but also encompasses human relationships with God, fellow beings, and nature. He highlights the importance of moral and spiritual values, as well as social responsibility in maintaining justice and balance. His approach is more inclusive, adapting to the pluralistic society and modernization dynamics in Indonesia. Through thematic and comparative analysis, this study finds that the differences in interpretation between the two scholars are significantly influenced by their social and ideological backgrounds. The findings indicate that khilafah is not only a political concept but also carries ethical and spiritual dimensions relevant to building a just and sustainable civilization. Thus, Surah Al-Baqarah verse 30 provides a philosophical foundation for humanity in fulfilling the mandate of khilafah in accordance with the demands of the times.